Digital Training in the Aeronautical Industry: Measuring the Usability of Two Mobile Applications - Smy, Phillip James; Donald, Iain; Scott-Brown, Kenneth; Falconer, Ruth E. (Frontiers in Computer Science, 2020)
The air traffic control industry is highly regulated, with stringent processes and procedures to ensure that IP (Intellectual Property) and workplaces are kept secure. The training of air traffic controllers (ATCs) and other roles relating to air traffic services is a lengthy and expensive process. The rate in which trainees can be trained is projected to fall significantly short of the demand for staff to work in the air traffic industry. This paper focuses on two prototype mobile training applications—Location Indicators (LI) and the Aircraft Control Positions Operator (ACPO) Starter Pack. LI and the ACPO Starter Pack have been produced to explore how air traffic control training could be improved and supported using digital applications. Each application explores a key learning area for trainees in the air traffic control industry and presents an alternative to the equivalent training that is currently in use. The two prototypes that have been designed focus on producing a succinct user experience alongside gamified elements to improve engagement. As part of this paper, usability testing has been undertaken with LI and the ACPO Starter Pack. A total of nine usability tests have been undertaken at four different locations. These usability tests consisted of participants from differing demographics, varying experience with the current training and differing amounts of time with both applications. The System Usability Scale (SUS) was adapted and used to quantify participant's reactions to the usability of each application. Usability scores for both applications were collected and then averaged to produce an overall score for each application. We can conclude from both usability scores and qualitative feedback that digital applications have the potential to engage future trainees in the air traffic services industry.